Pendampingan Evaluasi Kerusakan Jalan Lingkungan di Desa Pulau Terap - Islah, Muhammad; Desrimon, Arfi; Fitri, Arnanda Destia (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2022)
This community service activity aims to evaluate the damage to environmental roads in Pulau Terap Village, Kuok District, Kampar Regency. The road damage that occurs disrupts the mobility of residents and hampers the socio-economic activities of the community. The methods used include field surveys, visual observations, and community involvement in data collection and evaluative discussions. The types of damage found include potholes, cracks, surface deformation, and damage due to poor drainage. The evaluation results show that most road sections require immediate handling. This activity also encourages active participation of residents through mutual cooperation and reporting of road conditions, as well as providing an understanding of the importance of sustainable infrastructure maintenance. The evaluation data is expected to be the basis for more effective road repair planning by the village government.